The Angin of the Dalang in the Kelantan shadow play / Maszalida Hamzah - Hamzah, Maszalida (2014)
It is said that the journey of the Dalang of the Kelantan Shadow play is first and foremost determined by the existence of the Angin in him for without which, this vocation will not materialise. Once confirmed, he will undergo the basic, intermediate and advanced level of the ‘Way of the Dalang’. There are twelve types of Angin in the human that is divided into three. First is the Angin found in all Malay traditional arts inclusive of Wayang Kulit and Mak Yong. It is also present in the traditional Kelantan arts through lineage that includes Dalang Wayang Kulit (Malay Shadow play Dalang), Boinoh (healer) or Dukun, Bidan (midwife), Tukang Urut (masseur). The third is the Angin called Saka and this seem to point to the darker side of the Angin. This thesis is concerned only with the first and the second type of Angin while acknowledging the existence of the third. Angin is also said to be a concept of energy or soul or semangat, or nafsu that could also lead to pity or belas and intense pleasure or as an artistic temperament. Some Dalangs also added the word kehendak (will) as the Angin while agreeing to the word semangat (will), nafsu (ego/consciousness) and belas (Mercy) and nafas (breath). However, in all of the definitions above, none has explained in detail what the Angin is and how it is derived. The Angin of the Dalang in this research has been determined to reside in the Internal nowledge of the Dalang. Its presence is in the advanced training known as Sumpah Aturan Rahsia (The Oath of Secrecy). It consists of the process of'Penyatuan dan Penyebatian (Union and Subsistence), Pertapaan/ Meditasi (Meditation) and Mantera (Invocation). Through purposive sampling, the words uttered by the Dalang in the indepth interviews conducted and what is revealed about their training, before or pre-performance knowledge, the stories during the performances and the characters involved becomes the clues and signposts in developing the idea of the Angin within the Dalang. By applying the qualitative method which includes In-depth interview through the approach of Islamic Mysticism and Philosophy, the researcher is able to interprete the meaning {Ta’wil) of the Angin of the Dalang and its intrumentation internally and externally. It is found that the Angin of the Dalang is the spiritual principle guiding him in the process of menanggungpesaka (safeguarding tradition). This is seen as the survival kit that will determine the survival of the Dalang of the Kelantan Shadow play with Islam as its pillar.